The Role of Pseudomonas Spp in the Occurrence of Nosocomial Infections and the Current Status of Bacteriological Diagnosis - Nafisa, Fayziyeva (Journal of Innovation in Education and Social Research, 2025)
Hospital-acquired infections (HAIs), also known as nosocomial infections, are one of the most important problems in the healthcare system. These infections often occur in hospitalized patients during medical procedures or as a result of prolonged hospital stays. HAIs not only pose a threat to patient health, but also lead to increased treatment costs, longer hospital stays, and increased mortality.